Adaptation and reorganisation of primary care facility during COVID-19 pandemic: a perspective from primary health care corporation, Qatar - Shaik, Abdul Bari; Shaik, Noor Fathima; Al Majid, Shawqiya Salman; Sheik, Sanaulla (International Journal Of Community Medicine And Public Health, 2020)
The COVID-19 pandemic has brought unprecedented challenges to healthcare systems across the world. It has had a devastating impact on peoples’ health, well-being and livelihood, crippling the economy, aviation, travel, hospitality and various other sectors. In order to curb its impact various governments had to take drastic measures to deal with this crisis. In Qatar, the major healthcare providers led by the MOPH responded swiftly by implementing major changes. They developed infrastructure, revisited public health policies, modified their operations and functioning which helped to cope with this evolving public health emergency. This paper reviews how a small health center in Qatar had to adapt its services, infrastructure and pathways to the changing needs and demands in a timely fashion leading to improved patient care and helping to contain the outbreak in both patients and staff alike. It also evaluates how Primary health care corporation at an organization level paved the transition in every aspect to ensure efficient and safe delivery of primary care services to everyone. As the world is preparing to overcome the pandemic, the paper highlights the value of teamwork in responding to the adversity by creating innovative ways of working and how good leadership can have a positive influence on healthcare and society in general.